PENGARUH LEMBAGA PENDIDIKAN AGAMA ISLAM TERHADAP TOLERANSI ANTAR UMMAT BERAGAMA DI MASYARAKAT - Noperida; Atika Jamil Harahap; Sulhan Efendi Hasibuan (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2024)
Education in Indonesia is an organizing factor that cannot be separated from an institution where it is one of the contributions to Islamic education which can realize development and progress in an Islamic educational institution in the world of education. This can confirm that education can run well when the education system plays an active role in holistic, integrative institutions and also their implementation. The research aims to describe the types of institutions in Islamic education, especially in Indonesia and the role of Islamic education in supporting educational progress in Indonesia. There are three questions that need to be known, including Researchers must use a literature approach, a review, for use in research, namely as a source and material tool that will be used for a qualitative based research approach. This can be done as an exploration of a number of data, both primary data and secondary data, by following a strategy to increase reading of references from journals, books related to systems in a government institution. For this reason, in the journal, researchers discuss understanding the meaning of Islamic educational institutions and also the types of Islamic educational institutions